Performance of Ad-Hoc on-Demand Distance Vector Discovery Algorithms Based On Packet Lifetime - Ahmad, Noor Azlan (2008)
Ad hoc On-Demand Distance Vector (AODV) routing protocol is a reactive protocol in Mobile Ad hoc Network (MANET). AODV uses a distance or hop count for determining the best forwarding path and store the sequence number at table entry to ensure the path information is up-to-date. Although the AODV is a better performance compare to other proactive and reactive routing protocol in MANET, this routing still has a limitation and can to be improved. In this research, two algorithms that enhanced the original AODV are proposed. The first algorithm focuses on the AODV route table update management. The combination metrics of the lifetime and the sequence number in the table entry is used to solve the problem of the discarded active path information when the lifetime is expired. From the performance analysis, the proposed algorithm is successful to enhance the original AODV based on the performance of delay, overhead, packet delivery ratio and packet loss ratio. The second proposed algorithm is focused on the AODV route discovery. On the original AODV, packets will be allowed to rebroadcast the packet with a minimal lifetime. This will cause an unnecessary packets are discarded from the broadcasting. To solve this problem, Lifetime Ratio (LR) is proposed to reduce the unnecessary packets rebroadcast until it reaches the destination nodes. Based on the performance analysis, LR algorithm enhances the performance of the overhead, packet delivery ratio and packet loss ratio. The performance analysis of the proposed algorithms was conducted by using the discrete-event simulator, OMNeT++. The simulator was used to simulate the mobility environment and the Open System Interconnections (OSI) layers utilized in wireless simulation. To compare the performance between the original AODV and the proposed algorithms, the performance metrics are based on delay, overhead, packet delivery ratio, packet loss ratio and throughput. From the extensive simulations based on the performance metrics, the two proposed algorithms have shown distinct improvement and subsequently enhancing the performance of AODV.